1996
DOI: 10.1073/pnas.93.9.3942
|View full text |Cite
|
Sign up to set email alerts
|

Metalloelastase is required for macrophage-mediated proteolysis and matrix invasion in mice.

Abstract: Macrophages secrete a variety of proteinases that are thought to participate in remodeling of the extracellular matrix associated with inflammatory processes. We have eliminated expression of the macrophage metalloelastase (MME) gene by targeted disruption to assess the role of this protein in macrophage-mediated proteolysis. We found that the macrophages of MME-deficient (MME -/-) mice have a markedly diminished capacity to degrade extracellular matrix components. In addition, MME -/-macrophages are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
342
1
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(371 citation statements)
references
References 23 publications
22
342
1
6
Order By: Relevance
“…This observation is consistent with a reference to unpublished results suggesting MMP-12 limits lung metastasis growth in a LLC model (15). MMP-12-null mice have shown an impairment of macrophage infiltration into basement membrane in vivo (16). However, we found a similar number of macrophages in control and MMP-12-null mice in tumor-bearing lungs (data not shown), suggesting that macrophage infiltration is not impaired in our model.…”
Section: Resultssupporting
confidence: 78%
“…This observation is consistent with a reference to unpublished results suggesting MMP-12 limits lung metastasis growth in a LLC model (15). MMP-12-null mice have shown an impairment of macrophage infiltration into basement membrane in vivo (16). However, we found a similar number of macrophages in control and MMP-12-null mice in tumor-bearing lungs (data not shown), suggesting that macrophage infiltration is not impaired in our model.…”
Section: Resultssupporting
confidence: 78%
“…Consistent with the notion that MMP are involved in the breakdown of extracellular matrix compounds, MMP-12 knockout studies have shown that macrophages lacking MMP-12 have a reduced capacity to migrate through the matrix and display reduced elastolytic activity [63]. More recently, several studies have shown that MMP can modulate chemokine activities, either by modifying chemokines on the protein level or by regulating the formation of chemokine gradients (reviewed in [64]).…”
Section: Discussionmentioning
confidence: 76%
“…Macrophages of MME-/-mice have a markedly diminished capacity to degrade ECM components. MME-/-macrophages are essentially unable to penetrate reconstituted basement membrane in vitro or in vivo (Shipley et al, 1996).…”
Section: Discussionmentioning
confidence: 97%